A new approach in three dimensions to define pre- and intraoperative condyle–fossa relationships in orthognathic surgery – is there an effect of general anaesthesia on condylar position?. Issue 10 (October 2020) - Quast, A.; Santander, P.; Trautmann, J.; Moser, N.; Schliephake, H.; Meyer-Marcotty, P.
Abstract: Incorrect registration of the condylar position in orthognathic surgery is supposed to cause postoperative relapse, condylar resorption and temporomandibular disorders. The aim of this prospective study was to evaluate the influence of general anaesthesia on centric relation (CR). Therefore, CR registered preoperatively in the awake patient and CR registered intraoperatively under general anaesthesia were recorded in 30 patients (14 men, 16 women) undergoing orthognathic surgery (skeletal class I: n  = 3, II: n  = 13, III: n  = 14; symmetric: n  = 20; asymmetric: n  = 10). CR records were digitized and, through superimposition on the preoperative cone beam computed tomography of the patient's skull, the superior, anterior and posterior joint space and the volumetric congruence of 120 condyles were analysed. The linear measurements of joint spaces did not demonstrate any clinically relevant discrepancy between the CR measured in the awake and anaesthetized patient. In contrast, volumetric analysis revealed statistically significant differences between both states, with an intraoperative condylar sag predominantly in the posterior–inferior direction. The patient's skeletal class or symmetry had no significant influence on the intraoperative condylar displacement. Thus, the risk of fixing the condyle in an unphysiological position supports the idea of using intraoperative condylar positioning devices to achieve predictable and stable outcomes.